ISLAMIC LAW IN STATE LIFE OF BRUNEI DARUSSALAM - Abdurrahman Raden Aji Haqqi (Universitas Islam Negeri Raden Fatah Palembang, 2017)
The Kingdom of Brunei Darussalam is a country that makes Islam as the official religion of the State and Islamic law as a state administration system. This paper describes what forms of institutionalization of Islamic law in various aspects of national and state life in Brunei Darussalam and its role as a unifying force, peacekeeper, and state harmony, and the prosperity of the people. On the foundation of the ideology of the Malay Islamic Beraja (MIB) the establishment of Islamic law in the administration of state, government, and community life has begun since Sultan Hassanal Bolkiah has been named as Sultan until now. Various laws and regulations based on Islamic law governing various aspects of life have been produced and applied. All of this boils down to the goal of establishing the state of Baldatun Tayyibatun Wa Rabbun Ghafur or the State of Zikir (Remembrance) that produces prosperity in the world and the hereafter. The use of Islamic law in Brunei has been relatively beneficial for both aspects of order and structuring aspects of state and government as well as peace and well-being of the people.